Oxycodone for analgesia in children undergoing endoscopic retrograde cholangiopancreatography: a randomized, double-blind, parallel study - Ji, Wei; Sun, Liping; Huang, Yue; Bai, Jie; Zheng, Jijian; Zhang, Kan (Frontiers in Pharmacology, 2025)
BackgroundPostoperative visceral pain is a common complication after endoscopic retrograde cholangiopancreatography (ERCP). In this study, we compared the analgesic and anti-inflammatory effects of oxycodone and fentanyl in children undergoing ERCP.MethodsA single-center, randomized, double-blind study was conducted at a tertiary care hospital affiliated with Shanghai Jiao Tong University. Eighty-two pediatric patients aged 2–18 years who were scheduled for elective ERCP were randomly assigned to receive either oxycodone (0.2 mg/kg) or fentanyl (2 μg/kg). The postoperative pain was evaluated after 10 min, 20 min, and 30 min in the post-anesthesia care unit (PACU) as well as 6 h and 24 h in the ward following ERCP. Additionally, inflammatory cytokines in the serum, including tumor necrosis factor (TNF)-α, interleukin (IL)-6, and IL-10 were examined by blood sampling at baseline, 6 h, and 24 h after ERCP.ResultsCompared to fentanyl, children receiving oxycodone had significantly lower pain scores at 30 min, 6 h, and 24 h after ERCP, while the scores at 10 and 20 min were similar in both groups. We also found that fewer patients had pain scores ≥3 at 6 h and 24 h after the procedure in the oxycodone group [36.6% (15/41) vs. 61.0% (25/41) at 6 h, 34.1% (14/41) vs. 58.5% (24/41) at 24 h, p = 0.027 for both cases]. Furthermore, fewer children in the oxycodone group had elevated inflammatory cytokines (IL-6 at 6 h and TNF-α at 24 h after ERCP) compared to the fentanyl group. The incidence of postoperative vomiting was also lower among children receiving oxycodone [14.1% (7/41) vs. 24.4% (10/41), p = 0.032].ConclusionOxycodone (0.2 mg kg−1) can provide effective analgesia and stable hemodynamics in children undergoing ERCP. This analgesic characteristic may be related to amelioration of inflammation after ERCP.Clinical Trial Registrationwww.chictr.org.cn, identifier ChiCTR2300074473.